The influence and implications of climate change and variability on Coffea arabica in the East African highlands: Mt. Kilimanjaro case study - Craparo, Alessandro Carmelo William; Asten, Piet J.A. van; Läderach, Peter R.D.; Jassogne, Laurence T.P.; Grab, S.W. (Association for Science and Information on Coffee, 2012)
The coffee growing regions on the slopes of Mt. Kilimanjaro have become progressively warmer and drier over the past 48 years. The minimum temperature is the predominant climatic variable which influences coffee yields over longer-term climatic change. In contrast, the amounts of rainfall and in particular the timing of rainfall at specific growth periods are the most important climatic variables governing coffee yields on the micro-climatic scale. The predicted increase in climate change (temperature) and variability (rainfall) in future may thus adversely affect yield and cause numerous sporadic and incomplete flowering periods, effectively decreasing the amount of fruit set.